Multiplicity of Rationalities in the Housing Sector of African and European Countries: A Review of Modern Non-Binary Approaches - Litvintsev, Denis (Sotsiologicheskoe Obozrenie / Russian Sociological Review, 2024)
The main idea of the article is to review various theoretical and methodological approaches to the study of housing problems, which are based on the classical notions of rationalities’ multiplicity set mainly by Max Weber in the framework of his economic-sociological approach, as well as Mary Douglas in the framework of socio-cultural anthropology. To implement this task, the author of the article, taking an interdisciplinary position, refers to contemporary studies of the housing sector’s rationalities in different countries, mainly in Africa and Europe. Despite the lack of a direct connection between different studies, the unanimous refusal of the dichotomy “rational — irrational” in the analysis of housing processes was confirmed by the representatives of various disciplines. At the same time, the difference of approaches lies at the level of rationality (civilizational, national, urban, etc.) analysis, in the explored subject of social actions (the state, entrepreneurs, etc.), as well as in the features of researchers’ methodological positions themselves (behavioral economics, neo-institutionalism, etc.). In conclusion, M. Weber’s legacy is outlined as playing a decisive role for the shaping of ideas about the multiplicity of rationalities in housing research.